Association between the frequency of disposable diaper changing and urinary tract infection in children - Meirina Daulay; Rosmayanti Siregar; Oke Rina Ramayani; Supriatmo Supriatmo; Rafita Ramayati; Rusdidjas Rusdidjas (Indonesian Pediatric Society Publishing House, 2013)
Background Urinary tract infection (UTI) is the most common cause of fever in children. Less frequent disposable diaper changing is thought to be a cause ofUTI in children. While wearing a diapei; the perinea! area becomes damp with urine allowing bacteria to migrate from the anus to the external urethral orifice. Objective To assess for an association between the frequency of disposable diaper changing and urinary tract infections in children. Methods This cross-sectional study was conducted in the children's outpatient clinic of Haji Adam Malik Hospital from April to June 2010. Urine culture was performed in children with suspected UTI who wore disposable diapers every day. Subjects' ages ranged from 2 months to 2 years 6 months, with samples matched and collected by consecutive sampling. Diagnosis ofUTI was based on urine cultures with bacterial count 2:: 105/mL. Eighty children were followed in this study and divided into two groups: positive (n=40) and negative (n=40) urine cultures. Chi square test was use d to analyze the association between the frequency of daily disposable diapers changing during a one week period and the urine culture results. Results The frequency of daily disposable diapers changing in 80 subjects was as follows: < 4 times (22.5%), 4-5 times (40%), and 2::6 times (37.5%) . The frequency of daily disposable diaper changing in children with positive urine culture was as fo llows: < 4 times (1 8 out of 40), 4-5 times (22 out of 40), and 2::6 times (O out of 40); (P < 0.0001). The most common bacterial species found in urine cultures was Escherichia coli. Conclusion Lower frequency of daily disposable diaper changing is significantly associated with higher UTI incidence in children.